RANCANG BANGUN ALAT MONITORING DAYA DENGAN HMI BERBASIS ARDUINO UNO SEBAGAI OPC - Resa Pramudita; Neris Peri Ardiansyah (Universitas Widyatama, 2021)
Electricity is one a thing that always needed in technological development. Every house has a maximum power that operate at the same time. If the use is over the electrical power that the house have, automatically ACB will cut electric line in that house. This project developing a device to control power using a computer with arudino uno as OPC. Sensors that are used are current sensor ACS712, and voltage sensor ZMPT101B as a sensor to determine the power at the load. This device working automatically and controlled by a computer.